KESIAPAN PESERTA DIDIK MENGHADAPI MASA PUBERTAS DAN LAYANAN BK DI KELAS VII SMP NEGERI 31 PADANG - Pratiwi, Nadia; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
This study departed from the phenomenon lack of readiness students to face puberty change primary and secondary sex and ,Guidance and counseling services in schools. The objective is to describe: students readiness in the face of changes in primary and secondary sex at puberty, Readiness of , Guidance and counseling services teacher provides services for students to face puberty related with primary and secondary sex changes. This research is descriptive quantitative researches with population of whole studentss who have not yet faced of puberty in class VII Junior High School 31 Padang with sample 72 people consist of 35 male students and 37 female students. This research use purposive sampling. The data is collected through questionnaire. Data analyzed using percentage. Based on the research, it is found students readiness to face puberty related changes in sex primer, female students have highest percentage is 67.57% and remaining 45.71% for male students. It means male students and female students belong to the category very ready, while the studentss readiness to face puberty related changes in  secondary sex, male students have highest percentage is 82.86% and the second highest percentage is 67.57% for female students. Readiness of , Guidance and counseling services teacher provides services to studentss in  facing puberty related with changes in the primary sex shows male students have highest percentage is 75.68% belong to the category very ready and female students is 67.57% belong to the category very ready too, while readiness of BK teacher  provides services to students in facing puberty related with changes in secondary sex, female students have highest percentage is 75.68% belong to the category very ready and remaining 54.29% is male also belong to the category very ready.